The Long-Term Impact of Paid Parental Leave on Maternal Health and Subjective Well-Being - Katharina Heisig (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper studies the long-term impact of a paid parental leave reform in former East Germany in 1986 on maternal physical and mental health and subjective well-being. The reform extended paid leave for first-time mothers by six months to a maximum of twelve months. I use representative survey data from the German Socio-Economic Panel and a difference-in-differences design in a quasi-experimental setting. Results show that the effects of the reform were negligible on maternal long-term physical and mental health and subjective well-being. There is weak, but not robust, evidence for increased satisfaction with household activities, income, and work.
Keywords: I12; J13; J16; 330; social policy; parental leave; mental health; physical health; subjective well-being